Spies - Korte, Barbara (2023)
Abstract: Through fictional portrayals – in literature, film and television, comics and computer games – the secret actions of spies become public and can then (potentially) be heroized. However, fictional spies are usually precarious and ambiguous heroes because their deeds, insofar as heroic qualities can be attributed to them at all, are performed in moral grey areas. This makes the spy character suitable for a critical and sceptical negotiation of heroism